Melioidosis in a Returned Traveller. Issue 4 (2014) - Chagla, Zain; Aleksova, Natasha; Quirt, Jaclyn; Emery, Joel; Kraeker, Christian; Haider, Shariq
Abstract : Melioidosis is an infection endemic to Southeast Asia and Northern Australia, and is associated with significant morbidity and mortality. The present report describes a case of chronic melioidosis in a returning traveller from the Philippines. Clinical suspicion of this illness is warranted in individuals with a history of travel to endemic regions. Safety in handling clinical specimens is paramount because laboratory transmission has been described.